National priorities and national solutions to advance pharmacy worldwide across science, practice, education and workforce development - Duggan, Catherine (Archives of Pharmacy, 2022)
The COVID-19 pandemic has changed the way we work across the globe, especially where travel and face to face meetings were concerned. At FIP, we adapted by focussing on digital engagement with our members, capturing the voice of our members, learning about their priorities and challenges, as well achievements and accomplishments. We worked with members to identify national, regional perspectives, priorities and achievements. We were then able to respond with support, advocacy, guidance and collaboration with all members across all regions. FIP sought to align all priorities with the 21 Development Goals and then to identify strategies to share best practice, identify commonalities in terms of needs and potentially provide a platform for sharing experiences to support nations to advance pharmacy worldwide, across science, practice and the workforce. We sought to engage across our Academic Institution Members, our regional Pharmaceutical Forums and Member organisations. Each priority and practice exemplar is mapped to the FIP DGs so we map what is needed, what is delivered across the 21 goals so that pharmacy can deliver against the Astana Declaration and take our position in primary health care to delivery Universal Health Coverage for all. FIP can only deliver its mission and realise its vision in solidarity with members and stakeholders everywhere. By capturing our members voice, FIP has listened not only to learn but to contribute and deliver to transform pharmacy where needed.